2013
DOI: 10.1111/acem.12186
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Pregnancy Testing Among Adolescent Emergency Department Visits

Abstract: Objective To estimate the frequency of pregnancy testing among adolescent emergency department (ED) patients and to determine factors associated with testing. Methods This was a retrospective cross-sectional study using the National Hospital Ambulatory Medical Care Survey (NHAMCS) from 2005-2009 of ED visits by females ages 14 to 21 years. We estimated the frequency of pregnancy testing among all visits, those for potential reproductive health complaints, and those associated with exposure to potentially ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
0
8
2
Order By: Relevance
“…12 Although these guidelines exist, one study suggests that adolescents exposed to computed tomography (CT) radiation have lower than expected rates of pregnancy screening. 13 This study has not been confirmed by other reports.…”
Section: Introductioncontrasting
confidence: 79%
See 2 more Smart Citations
“…12 Although these guidelines exist, one study suggests that adolescents exposed to computed tomography (CT) radiation have lower than expected rates of pregnancy screening. 13 This study has not been confirmed by other reports.…”
Section: Introductioncontrasting
confidence: 79%
“…Variation in pregnancy screening existed not only between hospitals but also within a hospital by cohort type (ALL, AML, and ER). Although earlier studies suggested regional variation in pregnancy screening 13,21 and practice variation across centers has also been described for supportive-care measures such as analgesia administration in pediatric cancer patients, 22,23 to our knowledge, no prior reports have demonstrated different intracenter practice variation in pregnancy screening. Future work should focus on elucidating the factors responsible for both intercenter and intracenter variation in pregnancy screening, such as academic hospital status, hospital volume, affiliation with an adult hospital, and hospital environment (urban vs rural).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our independent variable was ED type. A pediatric ED was defined as an ED with >75% of visits made by patients ≤21 years old . Other EDs were considered general EDs.…”
Section: Methodsmentioning
confidence: 99%
“…Good communication with ED providers and administrators was critical to problem recognition and resolution. Because many ED clinicians are reluctant to provide sexual health care or provide suboptimal care, [21][22][23] we used a dedicated health educator to deliver the intervention. We obtained funds to pay for this position for a limited time; but this may not be possible at many sites, and funding this position is a barrier to sustainability.…”
Section: Innovative Intervention Targeting Sexual Healthmentioning
confidence: 99%